A chip-size antenna for wireless EEG - Correia, J. H. (2005)
This paper presents the design and characterization of a patch antenna built on lossy substrates compatible with integrated circuits fabrication. Two different substrates were used for antenna implementation: high-resistivity silicon (HRS) and Corning Pyrex #7740 glass. The antenna prototypes were built to operate close to the 5 GHz ISM band where applications like HIPERLAN and IEEE802.11a are standardized. They operate at a center frequency of 5.705 GHz (HRS) and 5.995 GHz (Pyrex). The application is a wireless wearable electroencephalogram (EEG) braincap. Wireless EEG allows patients to wear the braincap and maintain their mobility while simultaneously having their electrical brain activity monitored.